Efektivitas Model TGT Berbantuan Media Ular Tangga Berbasis Kearifan Lokal Kudus Terhadap Pemahaman Konsep Matematis Siswa - Ningrum, Septi Ayu Widia; Astuti, Kustina Puji; Darmasari, Zumroh Kusuma; Fais, Qurrotu A'yunina; Amaliyah, Fitriyah (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2025)
The low understanding of the concept of multiplication in elementary school students is an important concern in learning mathematics. This study aims to determine the effectiveness of interactive snakes and ladders media with local wisdom Kudus through Teams Games Tournament (TGT) type cooperative learning model in improving understanding of mathematics concepts, especially multiplication, in grade 3 students. This study used a quantitative approach with a quasi-experimental design. The study population was all grade 3 students who totaled 25 students, with a sample of 15 students selected through random sampling technique. The instruments used include questionnaires and observation sheets, while the data analysis technique uses statistical tests to compare pre-test and post-test scores. The results showed a significant increase in students' understanding of mathematics concepts, indicated by the difference in the average pre-test and post-test scores of 43.74 points. The significance test showed a p value <0.05, which means that the use of interactive snakes and ladders media is effective in improving student learning outcomes.